2014
DOI: 10.2298/vsp120423057m
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in adults in the Sumadija district, Serbia: A cross sectional study

Abstract: A continuous increase of patients with hypertension, coupled with the developed complications and increase in cardiovascular diseases as a cause of death, points to the lack of effective access to prevention and early detection of these diseases in the primary health care among the risk groups in Sumadija.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Diabetes mellitus prevalence in the general population is 6.7–7.4% in Poland, England and the USA, up to 10.8% in Spain and 18.8% in India, and HTA prevalence is 27.1–34.1% in the USA, Poland and England and up to 42.4–43.1% in Spain and India ( 13 , 15 , 27 , 29 ). In Serbia, the study by Marinkovic et al (33) indicated HTA prevalence of 53%, where 20.1% of the examinees had previously diagnosed HTA and another 32.4% of the examinees had survey high SBP and/or DBP. Somewhat higher HTA prevalence was found in female examinees.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus prevalence in the general population is 6.7–7.4% in Poland, England and the USA, up to 10.8% in Spain and 18.8% in India, and HTA prevalence is 27.1–34.1% in the USA, Poland and England and up to 42.4–43.1% in Spain and India ( 13 , 15 , 27 , 29 ). In Serbia, the study by Marinkovic et al (33) indicated HTA prevalence of 53%, where 20.1% of the examinees had previously diagnosed HTA and another 32.4% of the examinees had survey high SBP and/or DBP. Somewhat higher HTA prevalence was found in female examinees.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in Western countries report considerably lower prevalence of HTN: 19.5% in Canada, 29% in USA, 30% in England [12], 42.6% in Spain [13], as well as in China (32.5%) [14]. Nevertheless, certain districts of Serbia showed higher HTN prevalence (53%) [15]. …”
Section: Discussionmentioning
confidence: 99%